Balancing Roles: A Study of Work-Family Spillover among Working Mothers in Jakarta - Tambunan, Fauziah Hannum; Ginting, Henndy (Journal of Business and Management, 2019)
There is still an underlying perceptions regarding women role. In Indonesia, women are often assume as a back friend which means women are subordinate of men. In context of working, women are expected to do the household chores while men are working. However, women participation rate as worker in Jakarta is increasing rapidly from time to time making women have multiple roles; being a mother and a worker. This research will examine the effect of these roles whether it brings a positive or negative effect using the approach of spillover namely work-family positive spillover, work-family negative spillover, family-work positive spillover and family-work negative spillover. The data is obtained through a questionnaire answered by 212 working mothers in Jakarta. The four dimensions of work-family spillover have a significant value to dual role (role gratification and role strain) in Pearson correlation at the level of 0,01 and 0,05. Later, researcher further the analysis by conducting multiple linear regression and found that family-work spillover has an influence to the role gratification and role strain experienced by working mothers in work domain. In contrary, the work-family spillover is highly favored in role gratification rather than role strain. From the analysis, it is found that family-work domain is an important role in the work-family interface.